The therapeutic potential of acetyl-lysine and methyl-lysine effector domains - Brennan, P; Filippakopoulos, P; Knapp, S (2012)
Epigenetic reader domains are protein interaction modules that selectively recognize common post-translational modification on histones and other nuclear proteins such as ε-N-acetylated lysine or methyllysine/arginine residues. Interactions mediated by these effector domains result in the recruitment of gene specific transcriptional regulators. This review focusses on reader domains that recognize acetylated and methylated lysine and arginine residues. Bromodomains selectively recognize acetylated lysines residues and inhibitors have recently emerged as promising lead compounds for the treatment of cancer and inflammatory diseases, acting by specifically repressing expression of oncogenes and pro-inflammatory cytokines. Initial inhibitors have also been reported for methyllysine binding domains. Here we review recent development of this emerging target area. © 2012 Elsevier Ltd. All rights reserved.